Autonomous Vehicles as a Category of Transport Law: Definition and Classification - N. Demyanov, Dmitry; V. Krivenkova, Maria; A. Musabirova, Dinara (International Journal of Engineering and Technology, 2018)
In this paper, the authors consider issues related to the legal definition and understanding of the essence of vehicles with assisted driving and varying degrees of automation. It is pointed out on the need to study the terminological features and definitional difficulties in this area in order to optimize the current Russian transport legislation. The world experience of practical use of vehicles with assisted driving, as well as the legal regulation of related issues is analyzed. The characteristics of various types of automated vehicles are given and investigated. There are considered the current proposals for making amendments to the Rules of the road, aimed at regulating the legal status of unmanned vehicles. The imperfection of these additions, which do not take into account the presence of various levels of vehicle automation, is substantiated. An alternative approach to the formation of an effective conceptual apparatus based on the degree of automation of the driving process is proposed.Â Â Â